Kajian Kitab Manhaj Zawi al-Nazhar Syarh Manzumah ‘Ala al-Atsar Karya Syaikh Mahfuz al-Tarmasi: Analisis Sistematis dan Metodologis - Amri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This article aims to examine the book Manhaj Zawi al-Nazhar by Sheikh Mahfuz al-Tarmasi. The method used in this research is descriptive-analytical, focusing on how the book's systematics and methodology (dirasah ma fi al-kitab) are structured, rather than emphasizing dirasah ma haula al-Kitab, which encompasses the author's broader perspective. The results of the study indicate that the systematic approach used by Sheikh Mahfuzh in writing the book Manhaj Zawi al-Nazhar is similar to that of Al-Suyuthi, namely a combination of Ibn Shalah's method of prioritizing the classification of Hadith based on their quality, followed by the sequence and branches of ulum al-Hadith according to Ibn Hajar. The difference is that Sheikh Mahfuzh breaks down the discussion of the branches of Ulum al-Hadith into 81 branches, from the 69 branches of Ulum al-Hadith found in Al-Suyuthi's Alfiyah. The method of explaining the book Manhaj Zawi al-Nazhar, as seen from the structure of the explanation, uses the detailed explanation method or comprehensive explanation. However, when viewed from the approach used in the explanation, the book Manhaj Zawi al-Nazhar employs a linguistic explanation method, which can also be referred to as a comprehensive explanation method. This research has the urgency of enriching Islamic studies in the field of methodology. By enriching the methods used in Islamic studies, this will lead to an increase in Islamic scientific knowledge.